화학사고 응급정보 제공을 위한 환경부의 정보시스템 구축 - 박춘화; 노혜란; 박윤신; 김성범; 석광설; 최경희 (한국재난정보학회 논문집, 8(2), 2012)
화학물질의 사용량 증가에 따라 일반국민이 화학물질 또는 화학제품에 노출되는 사례가 빈번하게 발생하고 있어 응급정보 제공 수요가 급증하고 있으며, 신규 화학물질의 도입에 따라 화학물질 정보의 지속적인 구축 필요성이 제기되고 있다. 이에 따라, 환경부는 국내 유통 중인 화학제품 중심으로 상세물질정보를 지속적으로 확충하여 일반국민에게까지 정보제공 범위를 확대하는 화학사고 응급대응정보시스템 구축사업을 단계적으로 추진하여 왔다. 이를 통해 24시간 정보제공이 가능하도록 웹 서비스 기반을 마련하여 화학제품 또는 화학물질에 노출된 일반인 또는 현장 대응요원에게 실효성 있는 응급대응정보가 전달될 수 있도록 정보시스템을 구축하여 운영하고 있다. Owing to the increase of chemical usage, ordinary people are frequently exposed to chemicals and chemical products. Thus, demand on emergency response to chemical accidents is rapidly increasing. Also, as new chemicals continue to be introduced to the market, information system on chemicals need to be consistently updated. Under the circumstances, the MOE(Ministry of Environment) has established a comprehensive 24-hour web-based CEIS(Chemical accident Emergency response Information System) which contains more various material information for wider range of users from governmental organization to the general public. KCI Citation Count: 0